Fauna and land reclamation technology - a review of the history and need for such studies - Majer, Jonathan (1989)
There is clearly a need to bring together the current knowledge about the ways in which fauna may contribute to reclamation technology. This book was written to fill this gap in the literature. It describes how the presence of certain animals can assist, or impede, the process of ecosystem restoration and also how reclamation may be designed to cater for economically or aesthetically valuable species such as fish, cattle or wildlife. It also discusses the implications to re colonization of such problems as toxic substrates, unfavourable climatic zones or pest outbreaks.